• Accueil
  • Math
  • 2m - n=3m + n=9 in linear equation by elimination...

2m - n=3
m + n=9
in linear equation by elimination ​

Answers

  • Réponse publiée par: meteor13

    Hello !!

    First you sum the equations to eliminate the [n].

    2m - n = 3

    +

    m + n = 9

    3m = 12

    Second, having eliminated the unknown [n] you solve the equation that came up to find the value of [m].

    3m = 12

    m = 12/3

    m = 4

    Third and last, you substitute the value of [m] you found in any of the equations and find the value of [n].

    m + n = 9

    4 + n = 9

    n = 9 - 4

    n = 5

    Final result : The solution for [m] is 4 and the solution for [n] is 5.

    I hope I have collaborated !

  • Réponse publiée par: snow01

    a

    Explanation:

  • Réponse publiée par: janalynmae

    answer:

    bat ang pogi ko talaga

    Step-by-step explanation:

    ang Pogi mo

Connaissez-vous la bonne réponse?
2m - n=3m + n=9 in linear equation by elimination ​...